1999
DOI: 10.1002/(sici)1096-9853(19990425)23:5<383::aid-nag977>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the vane test considering size and time effects

Abstract: An analysis of the vane test using an Arbitrary Lagrangian}Eulerian formulation within a "nite element framework is presented. This is suitable for soft clays for which the test is commonly used to measure in situ undrained shear strength. Constitutive laws are expressed in terms of shear stress}shear strain rates, and that permits the study of time e!ects in a natural manner. An analysis of the shear stress distributions on the failure surface according to the material model is presented. The e!ect of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It is the circumferential failure zone that gives the largest contribution to the measured torque (Wroth, 1984) and the cylindrical failure geometry around the vane is supported by the laboratory experiments of Cadling & Odenstad (1950) (low-sensitivity clay) and Arman et al (1975) (soft clay), as well as the numerical work of Alencar et al (1988), Griffiths & Lane (1990) and Perez-Foguet et al (1999). However, when analysing a silty clay using a laboratory vane, Wilson (1963) observed that the failure surface was almost square at the instant of maximum torque and that the full cylindrical surface did not develop until considerable deformation had taken place.…”
Section: Technical Notementioning
confidence: 99%
“…It is the circumferential failure zone that gives the largest contribution to the measured torque (Wroth, 1984) and the cylindrical failure geometry around the vane is supported by the laboratory experiments of Cadling & Odenstad (1950) (low-sensitivity clay) and Arman et al (1975) (soft clay), as well as the numerical work of Alencar et al (1988), Griffiths & Lane (1990) and Perez-Foguet et al (1999). However, when analysing a silty clay using a laboratory vane, Wilson (1963) observed that the failure surface was almost square at the instant of maximum torque and that the full cylindrical surface did not develop until considerable deformation had taken place.…”
Section: Technical Notementioning
confidence: 99%
“…(1) represents a very good estimate for cohesive strength of isotropic and non-softening soils. Pérez-Foguet et al (1999) performed an analysis of the vane test using an Arbitrary Lagrangian-Eulerian formulation within a finite element framework. They analysed the shear stress distributions on the failure surface and presented the dependence of shear band formation on the constitutive model selected.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, in some fields of solid mechanics, such as the modelling of forming processes, ALE fluid-based formulations are widely used. In the thesis, an ALE fluid-based formulation has been applied to quasistatic and dynamic simulations of the vane test for soft materials, see section 2.1 (Pérez-Foguet, Ledesma and Huerta 1999). This particular application is an example of how an ALE formulation allows to manage the movement of the boundary in a straightforward manner.…”
Section: Kinematic Formulationmentioning
confidence: 99%